Streptococcus pneumoniae serotype 3 is masking PCV13-mediated herd immunity in Canadian adults hospitalized with community acquired pneumonia: A study from the Serious Outcomes Surveillance (SOS) Network of the Canadian immunization research Network (CIRN). Issue 36 (23rd August 2019) - LeBlanc, Jason J.; ElSherif, May; Ye, Lingyun; MacKinnon-Cameron, Donna; Ambrose, Ardith; Hatchette, Todd F.; Lang, Amanda L.S.; Gillis, Hayley D.; Martin, Irene; Demczuk, Walter; Andrew, Melissa K.; Boivin, Guy; et al.
Highlights: The proportion of CAP attributed to S. pneumoniae declined from 2010 to 2014, but increased in 2015. PCV13 serotypes in bacteremic and non-bacteremic pneumococcal CAP mirrored trends seen for S. pneumoniae positivity. Herd immunity afforded by serotypes 7F and 19A was partly masked by a concomitant increase in the proportion of serotype 3. The shift in serotype distribution over time was not accompanied by changes in patient demographics or serious outcomes. Despite herd immunity, pneumococcal CAP and IPD remain substantial cause of morbidity and mortality in hospitalized adults. Abstract: Background: The 13-valent pneumococcal conjugate vaccine (PCV13) was recently shown to be effective against PCV13-type invasive pneumococcal disease (IPD) and pneumococcal community acquired pneumonia (CAPSpn ) in healthy adults aged ≥65 years, prompting many countries to re-assess adult immunization. In Canada, the potential benefits of adult PCV13 immunization were unclear given anticipated herd immunity from PCV13 childhood immunization introduced since 2010. This study describes the serotype distribution and clinical outcomes of Canadian adults aged ≥16 years, who were hospitalized with CAPSpn and IPD from 2010 to 2015. Methods: Active surveillance for CAP and IPD was performed in adult hospitals across five Canadian provinces. IPD was identified when Streptococcus pneumoniae was isolated from sterile sites. Bacteremic and non-bacteremic CAPSpn were identified using blood culture, and sputum culture or PCV13-specific urine antigen detection (UADPCV13 ), respectively. Serotype was assigned using Quellung reaction, PCR, or UADPCV13 . Results: Of 6687 CAP cases where a test was performed, S. pneumoniae positivity decreased from 15.9% in 2011 to 8.8% in 2014, but increased to 12.9% in 2015. CAPSpn attributed to PCV13 serotypes followed a similar trend, dropping from 8.3% in 2010 to 4.6% in 2014, but increasing to 6.3% in 2015. The decline was primarily attributed to serotypes 7F and 19A, and the proportional increase to serotype 3. Similar trends were noted for bacteremic and non-bacteremic CAPSpn . Serious outcomes such as 30-day mortality, intensive care unit admission, and requirement for mechanical ventilation were prominent in CAPSpn and IPD cases, but remained unchanged over the study years. Conclusion: Herd immunity afforded primarily by serotypes 7F and 19A appears to be partly masked by a concomitant proportional increase of serotype 3. Despite evidence of herd immunity, these PCV13 serotypes remain persistent in Canadian adults hospitalized with CAPSpn, and represent between 5 and 10% of all CAP in this patient population.